Analysis of Molecular Dynamics (MD) Simulation of Carbonic Anhydrase - Talei, Saeed; Hadjadj, Rachid; Mizsey, Péter; Owen, Michael C. (Hungarian materials and chemical sciences and engineering (Online), 2023)
Molecular Dynamics (MD) simulation is a computational method for analyzing the physical movements of atoms and molecules allowed to interact for a fixed duration of time. In this study, the thermal stability of carbonic anhydrase, which catalyzes the reaction of water and carbon dioxide, was investigated. Our simulations were performed in a box of water at four different temperatures, 300 K, 310 K, 320 K, and 330 K. The duration of each simulation was 100 ns, and thereafter the hydrogen bonds, Solvent Accessible Surface Area (SASA), as well as Root Mean Square Deviation (RMSD) were analyzed. Moreover, cluster analysis was done to identify representative structures at each temperature. The results showed that changing the temperature did not significantly impact the number of hydrogen bonds. The SASA had more fluctuation when the temperature increased. Moreover, the higher the temperature of the simulation was, the more clusters were obtained. The higher number of clusters indicates higher conformational flexibility and less-stable conformers forming during the simulation.